Techno-economic modeling of a novel poly-generation system based on biogas for power, hydrogen, freshwater, and ammonia production - Farhang, Behzad; Ghaebi, Hadi; Javani, Nader (ELSEVIER SCI LTD, 2023)
In the current study, a new poly-generation energy system run by biogas steam reforming is proposed and assessed. To dissect the techno-economic feasibility of the offered system, energy, exergy, and sum unit cost of the products (SUCP) are considered as robust indicators for the system appraisal. Also, to acquire enhanced thermodynamic efficiencies, the system has benefited from the careful design of the biogas steam reforming unit, modified Rankine cycle, ammonia synthesis unit, hydrogen generation equipment as well as reverse osmosis unit. It is uncovered that the prepared poly-generation system is qualified to provide 687.4 kW of power, 0.9662 kg/s of freshwater, 0.15 kg/s of hydrogen, and 1.149 kg/s of ammonia. Besides, the energy and exergy efficiencies of the system have been calculated at about 18.9% and 16.9%, respectively with a total exergy destruction rate of 51020.78 kW. Also, following the results of the thermodynamic appraisals, the biogas steam reforming reactor and ammonia synthesis reactor have the highest contributions to inefficiencies happening in the system. Furthermore, from a sweeping sensitivity investigation, the optimum performance of the system appears in a biogas steam reforming reaction temperature of 1050K. Also, the SUCP decreases by about 21 $/GJ by increasing the Biogas Steam Reforming reactor pressure.
Keywords: Biogas; Exergy analysis; Hydrogen; Ammonia; Poly -generation; MULTIGENERATION SYSTEM; PERFORMANCE ASSESSMENT; GAS-TURBINE; ENERGY; SOLAR; BIOMASS; OPTIMIZATION; EXERGY; DESALINATION; PARAMETERS; Science & Technology - Other Topics; Engineering; Environmental Sciences & Ecology